Body mass, training, menses, and bone in adolescent runners: a 3-yr follow-up - Barrack, M. T.; Van Loan, M. D.; Rauh, M. J.; Nichols, J. F. (Medicine & Science in Sports & Exercise, 2011)
Endurance runners with low bone mass during adolescence may risk attaining a low peak bone mineral density (BMD) in adulthood. Alternatively, they may mature late and undergo delayed bone mineral accumulation.